Sustainable forest management contribution to food security: A stakeholders' perspectives in Sabah, Malaysia - Walter Lintangah; Vilaretti Atin; Amirah Liyana Ibrahim; H Yahya; Elne Betrece Johnlee; R A Martin; G John (IOP Publishing Ltd., 2022)
Implementing Sustainable Forest Management (SFM) policy has contributed to conserving and protecting the forests to remain relevant for future generations. This study determines stakeholders' viewpoint on the relationship between the implementation of SFM and food security in Sabah. The study was conducted by distributing online questionnaires through the SurveyMonkey platform using convenience sampling methods. Most of the respondents agreed that the forestry sector is still relevant to the development and generation of the economy and revenue to the state of Sabah. Apart from nature-based tourism, wood-based manufacturing, furniture industry, and agroforestry practices, other potential economic-generation segments are indigenous forest food productions, such as wild honey, fruits, vegetables, and game animals. The forestry sector could contribute to food security for Sabah by advancing the current practices and the use of local resources of forest foods. Other prospects are integrating natural and plantation forest management programs with the generation of forest food resources. Factors that could foster the forestry sector's contribution to food security, among others, are research and innovation, education, involvement of local communities, and the role of government policy on forestry and food security in Sabah.